The EULAR-OMERACT joint-level scoring of ultrasound synovitis demonstrates good construct validity when tested at the patient-level in comparison with measures of disease activity and joint damage in patients with rheumatoid arthritis - Tan, York Kiat; Thumboo, Julian (Frontiers in Medicine, 2025)
ObjectivePatient-level ultrasound joint inflammation outcomes, derived from the European Alliance of Associations for Rheumatology-Outcome Measures in Rheumatology (EULAR-OMERACT) joint-level scoring of elementary components and the combined score (CS), were compared with measures of disease activity and joint damage in patients with rheumatoid arthritis (RA).MethodsClinical joint assessment and a 22-joint (bilateral hands/wrists) ultrasonography were performed independently during the same patient study visit. Patient-level ultrasound joint inflammation outcomes [total power Doppler (PD) score, total grayscale (GS) score, total CS, number of joint(s) with CS ≥ 2 (at least moderate synovitis), and number of joint(s) with ultrasound synovitis defined as PD > 0 or GS ≥ 2] derived from the EULAR-OMERACT joint-level scoring system were correlated with Clinical Disease Activity Index (CDAI), 28-joint disease activity score (DAS28), and ultrasound-detected joint damage, i.e., total bone erosion score (TBES). The relationship between the variables was studied using simple linear regression.ResultsA total of 83 RA patients underwent scanning of 1,826 joints in this cross-sectional study. All patient-level ultrasound joint inflammation outcomes showed significant correlations (p < 0.01) with CDAI, DAS28, and TBES (with correlation coefficients ranging from 0.45 to 0.48, 0.38 to 0.45, and 0.66 to 0.83, respectively). A linear regression analysis revealed statistically significant relationships (p < 0.01) for all patient-level ultrasound joint inflammation outcomes in relation to CDAI, DAS28, and TBES (with regression coefficients ranging from 0.603 to 1.260, 0.066 to 0.149, and 0.416 to 0.818, respectively).ConclusionPatient-level ultrasound joint inflammation outcomes, derived from the EULAR-OMERACT joint-level scoring system, showed good construct validity when compared to both disease activity and joint damage in patients with RA.